Flywheel eccentric overload exercises versus barbell half squats for basketball players: Which is better for induction of post-activation performance enhancement? - Hezhi Xie; Wenfeng Zhang; Xing Chen; Jiaxin He; Junbing Lu; Yuhua Gao; Duanying Li; Guoxing Li; Hongshen Ji; Jian Sun (PLoS ONE, 2022)
Objective This study compared the post-activation performance enhancement (PAPE) effects of a flywheel eccentric overload (FEOL) exercise and barbell half squats (BHS) on countermovement jump (CMJ) and 30 m sprint performance. Methods Twelve male collegiate competitive basketball players were enrolled in this study and they implemented two training protocols: barbell half squat (BHS) and flywheel eccentric overload (FEOL) training. The BHS protocol included three intensities of load: low (40% 1RM), medium (60% 1RM), and high (80% 1RM), with each intensity consisting of 5 sets of 3 repetitions. The FEOL protocol included three inertia intensities: low (0. 015 kg∙m2), medium (0.035 kg∙m2), and high (0.075 kg∙m2), with each intensity consisting of 3 sets of 6 repetitions. The measurement time points were before training (baseline) and at 3, 6, 9, and 12 minutes after training. A two-stage (stage-I and stage-II) randomized crossover design was used to determine the acute effects of both protocols on CMJ and sprint performance. Results At each training intensity, the jump height, jump peak power output (PPO), jump impulse and 30m sprint speed at 3, 6, 9, and 12 minutes after BHS and FEOL training did not change significantly compared to the baseline. A 2-way ANOVA analysis indicated significant main effects of rest intervals on jump height, jump PPO, and jump impulse, as well as 30m sprint speed. The interaction of the Time × protocol showed a significant effect on jump height between BHS and FEOL groups at high intensity in stage-I (F = 3.809, p = 0.016, df = 4) and stage-II (F = 3.044, p = 0.037, df = 4). And in high training intensity, the jump height at 3 (7.78 ± 9.90% increase, ES = 0.561), 6 (8.96 ± 12.15% increase, ES = 0.579), and 9 min (8.78 ± 11.23% increase, ES = 0.608) were enhanced in I-FEOL group compared with I-BHS group (F = 3.044, p = 0.037, df = 4). In stage-II, the impulse and sprint speed of the FEOL group were significantly higher than those of the BHS group at 6, 9, and 12 min under low (FEOL = 0.015kg∙m2, BHS = 40%1RM), medium(FEOL = 0.035kg∙m2, BHS = 60%1RM), and high (FEOL = 0.075kg∙m2, BHS = 80%1RM) intensities. Furthermore, the sprint speed of the two training protocols did not change at different time points. The interaction of Time × training intensity showed lower sprint speeds in the II-BHS group at a high intensity (BHS = 80%1RM) compared to low (BHS = 40%1RM) and medium (BHS = 60%1RM) training intensities, especially at 9 min and 12 min rest intervals. Conclusion Although barbell half squat training and flywheel eccentric overload training did not provide a significant PAPE effect on explosive power (CMJ and sprint) in male basketball players, FEOL training showed a better potential effect on enhanced CMJ jump performance at the high training intensity.